Immunomodulatory Effects of Modified Colostrum, Whey, and Their Combination With Other Natural Products: Effects on Natural Killer Cells - Xuesheng Han, MS; David Vollmer, MS; Xuefei Yan, MS; Yahong Zhang, MS; Mingfa Zang, MPVM; Chenfei Zhang, MS; Catherine M. Sherwin, MS; Elena Y. Enioutina, MS (Current Therapeutic Research)
Objectives: Natural killer (NK) cells are important immune system effector cells providing innate defenses against intracellular infections, including viral infections, immune surveillance, and cancer immunoediting. The primary purpose of this study was to investigate whether modified ultra-filtrated colostrum (UC) and hydrolyzed whey (W) products or their combinations with other natural products with reported immunomodulatory properties will stimulate NK cell cytotoxic activity by activation of granzyme B and IFN-γ production. Methods: The ability of study products to stimulate the cytotoxic activity of human-purified CD56+ NK cells and the production of granzyme B and IFN-γ by activated NK cells was evaluated in the cytotoxic assay. Results: All study products significantly increased NK-cell cytotoxic activity at an E: T ratio of 20:1. Treatment of cells with UC had a maximal cytotoxic effect at the minimal dose of 10 µg/ml, which exceeded the cytotoxic activity of IL-2. In contrast, the addition of egg yolk (CE) or CE + botanical blend (CEB) to UC resulted in a dose-dependent cytotoxic response with a maximal response at 1000 µg/ml. The maximal activity of blend products was comparable to UC activity. W exerted minimal stimulatory activity on NK cells. The magnitude of granzyme B and IFN-γ production was closely associated with the cytotoxic activity of NK cells stimulated with the study products. Conclusions: All study products demonstrated stimulatory activity on NK cells, with UC having a maximal effect on NK cell cytotoxicity. The study products can be used as dietary supplements to support NK cell activity in healthy individuals.